(untitled) (American Journal of Islam and Society, 2002)
Fatimid intellectual production contains some remarkable personal memoirs that deserve a joint study. The Kitab al-MunaJ?arat (The Book of Discussions) by lbn al-Haytham is one example of this kind ofliterature. Abu ’Abd Allah Ja·far ibn Ahmad ibn Muhammad ibn al-Aswad ibn al-Haytham was a Qayrawani scholar of Sh???? i persuasion when the Fatimid caliphate was established in North Africa. In this Ki tab, he recorded his meetings and conversations with the leaders of the Isma·ili da·wah (mission) in the first months after the conquest ofQayrawan, from Rajab 296/March 909 until the appearance of the Imam al-Mahdi in Rabi’ II 297/January 910. Although the existence of this work had been known for some time, it is only now that we have at our disposal the complete Arabic text, together with an English translation, an introductory study, a bibliography and an index. Paul E. Walker is mainly responsible for having realized the importance oflbn al-Haytham’s text. Both he and W. Madelung, whose collaboration has been decisive in the final outcome, are the best qualified scholars ...